Pengaruh Karakteristik Dewan Direksi Terhadap Kinerja Keuangan Perusahaan Non Keuangan Yang Terdaftar di Bursa Efek Indonesia - Robert Jao; Fransiskus Randa; Anthony Holly; Leonardo Gohari (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2021)
This study aims to investigate the influence of the characteristics of the board of directors consisting of size, activity, gender, and experience of the board of directors on financial performance. The population of this study was non-financial companies listed on the Indonesia Stock Exchange from 2017 to 2019. The sample selection used a purposive sampling technique. The research data comes from the company's annual reports. The results show that the characteristics of the board of directors such as size and activity have a positive and significant impact on financial performance. However, characteristics of the board of directors such as gender and experience do not have a significant effect on financial performance.